The Role of Diklatsar in Shaping Militancy and Moral Character of Banser Cadres of Nahdlatul Ulama at SMA Pondok Pesantren Sunan Ampel Punggur - Agustian, Ferdi; Irhamudin; M. Sayyidul Abrori (Journal of Research in Islamic Education, 2026)
This study aims to describe and analyze the role of the Basic Education and Training (Diklatsar) of Barisan Ansor Serbaguna (Banser) in shaping the militancy and moral character of Nahdlatul Ulama (NU) cadres at SMA Pondok Pesantren Sunan Ampel Punggur. This research is motivated by the perception that Banser Diklatsar tends to emphasize physical training and semi-military discipline, thereby overlooking its role in value education, NU ideology, and moral development. The research problems focus on how Banser Diklatsar is implemented, how Islamic education values are internalized in the training process, and how Diklatsar contributes to the formation of cadre militancy and moral character. This study employs a qualitative approach using a descriptive-analytical method. Research data were collected through direct observation of Banser Diklatsar activities, in-depth interviews with Diklatsar participants, Banser instructors, pesantren administrators, and local NU officials, as well as documentation of relevant archives and organizational records. Data analysis was conducted using an interactive model involving data reduction, data display, and conclusion drawing. The findings indicate that Banser Diklatsar plays a significant role in fostering cadre militancy through the internalization of NU ideological values, discipline, organizational loyalty, and readiness to serve. In addition, Banser Diklatsar contributes to moral development through religious habituation, exemplary conduct of instructors, and the internalization of Islamic moral values (akhlaq al-karimah). Therefore, Banser Diklatsar functions as an integral medium of Islamic education in the NU cadreization process